Children with Learning and Behavior Problems: A Behavior Management Approach. (2nd ed.). - Kupietz, Samuel S. (American Journal of Mental Deficiency, 1979)
The article reviews the book "Children With Learning and Behavior Problems: A Behavior Management Approach," 2nd ed., by William I. Gardner.